Trabalhadores frente a perspectiva da aposentadoria - Carvalho, Thaís Araujo de Oliveira Pereira de (2018)
How have the Brazilian private-sector worker been preparing for retirement? This was the main question of this research, which started from the assumption that the entrance to the end of the career is in a place of unpreparedness, and consequently it entails damages to the old age, that now happens to be of a longer period. In order to understand this behavior, the following objectives were proposed: a) outline the sociodemographic profile of a group; b) identify if the interviewees had any planning for retirement - be it financial, leisure, study or other; c) understand their perception of concerning their old age and the project of life for their extended time, and d) contribute with inputs for the formulation of educational policies of planning for the post-work world. To respond to this problem, it was decided through a semi-structured analysis in a group of 40 private-sector workers, of the transformation business in São Paulo state, covering men and women over 41 years of age. Answers expressing surprise, high centrality at work, lack of knowledge and fear of facing the issue led to a scenario of interviewees, who were classified into three groups, according to the level of perception and behavior for retirement: those who are very unprepared, those semi prepared and those who deny or reject retirement. It was also identified that the old age has extremes meanings: negative and positive. The results indicates that the subject is not yet adequately addressed and has a lack of preparation in several spheres, denouncing not only a cultural issue, but also an impending public social problem for which we are rapidly moving towards in Brazil